Effects of Smokefree Class Competition 1 year after the end of intervention: a cluster randomised controlled trial. Issue 4 (11th November 2010) - Isensee, Barbara; Morgenstern, Matthis; Stoolmiller, Mike; Maruska, Karin; Sargent, James D; Hanewinkel, Reiner
Abstract : Background: The Smokefree Class Competition, a school-based smoking prevention intervention, is widely disseminated in Europe. Participating classes commit themselves to be smoke-free and self-monitor their smoking status. Classes that remain smoke-free for 6 months can win prizes. Effects of the intervention on current smoking, initiation and progression of smoking were investigated. Methods: Cluster randomised controlled trial. 84 schools (208 classes with 3490 students; mean age 12.6 years, 50.4% female) in Saxony-Anhalt, Germany, were randomly assigned to intervention or control condition. A baseline survey was conducted before the implementation of the programme, while post-test and follow-up surveys were carried out 7 (immediately after the end of the competition), 12 and 19 months after baseline. Effects of participation in the programme on current and lifetime smoking were analysed by multilevel models controlling for confounding variables. Results: Intervention students smoking occasionally at baseline smoked less frequently than students taking not part in the intervention at 7 and 12 months after baseline. Persistent beneficial programme effects were also found for lifetime smoking: intervention students were less likely to progress from experimental to established use. Conclusion: Data suggest that Smokefree Class Competition reduces the probability of progressing from occasional and experimental stages of smoking to more established forms of use. Clinical trials registration number: Trial registration ISRCTN27091233 in Current Control Trial Register.